The Influence of Self-Directed Dialog Toward Students’ Speaking Ability in SMAN 20 BATAM - Lala Imaliyah (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The objective of the investigation is to sort out the The Influence of Self-Directed Dialog Toward Students’ Speaking Ability in SMAN 20 BATAM at the eleventh grade students of the educational year 2023/2024. To achieve the objective, the exploratory arrangement was used in this assessment audit using one social occasion pre-test and post-test plan. Having involved 45 students of the eleventh grade the results uncovered that the on both the pre-and post-tests, the improvement got a common score of 2.28 percent. It was a striking accomplishment, especially when think about the 2.79 percent extension in talking. This result showed that there was a tremendous qualification between the understudies talking limit when the treatment was given. From the eventual outcome of the data examination it might be contemplated that the independent discourse method empower immense effect on talk. It will in general be seen from the score of the pre-test going before the treatment was given and the result of the post-test after the treatment was given. Besides the result similarly recommended that this strategy empowered a gigantic difference to talk when the treatment was given. Overall, it can finally be induced that autonomous talk method give basic effect towards the students’ of eleventh grade of SMAN 20 BATAM talking limit.